Belief systems, religion, and behavioral economics : marketing in multicultural environments - Minton, Elizabeth A.; Kahle, Lynn R. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
Religion is a topic that businesses often ignore, in spite of 70% of the world being religious. Whether the silence results from the taboo nature of the topic or the thought that religion is a separate domain from consumption and business, it cannot be denied that it has received scant attention. Many do not realize (or resist) the idea that religion is a key contributor to a consumer's core values, which then contribute to consumption decisions, voting practices, reaction to pro-social messages and public policy, as well as donating behavior.
Preface -- 1. Behavioral economics and belief systems -- 2. Demystifying belief systems -- 3. Belief systems of the western world & interpretations for behavioral economics -- 4. Belief systems of the eastern world & interpretations for behavioral economics -- 5. The disconnect between belief systems and behavioral economics -- 6. Comparing belief systems: influences on behavioral economics -- 7. Comparing belief systems: influences on consumers -- 8. Managerial implications for businesses -- 9. Cases -- 10. Conclusion -- Appendix -- Notes -- References -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 123-135) and index.
Title from PDF title page (viewed on January 3, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Economics -- Religious aspects; Economics -- Psychological aspects; Multiculturalism in advertising; Consumer behavior -- Religious aspects; religion; religiosity; religious affiliation; belief systems; Christian; Jew; Muslim; Hindu; Buddhist; Confucianist; Taoist; behavioral economics; consumer behavior; decision making; morality; donation behavior; sustainability; holidays; Electronic books